Intergenerational Communication in Bandung City: A Case Study of the Digital Divide in Local Communities - Sandi, Renda; Surya, Dhika (International Journal of Linguistics, Communication, and Broadcasting, 2025)
The digital divide between the younger and older generations has become an important issue in social communication in the digital era. This study investigates the differences in understanding and use of digital technology between generation Z, generation Y, and generation X/Baby Boomers in Bandung City. Using a descriptive qualitative approach with case studies, data were collected through in-depth interviews, participant observation, and surveys of 90 respondents. The results showed that the younger generations (Z and Y) have higher digital skills, especially in the use of social media and instant messaging applications, while generation X and Baby Boomers still rely more on face-to-face communication and telephone. This digital divide creates barriers in intergenerational communication, causes social isolation among the older generation, and limits their participation in wider social spaces. These findings suggest that interventions such as digital literacy training and the creation of inclusive spaces for intergenerational collaboration can reduce the digital divide and improve social communication. This study provides important insights into how the digital divide affects intergenerational relationships in Bandung City and suggests strategic steps to reduce the gap through education and technology empowerment programs.